Pengaruh Budaya Kerja, Disiplin Kerja dan Pengalaman Kerja terhadap Kinerja Pegawai pada Kantor Kecamatan Kendari Barat - Hasriani Hasriani; Abd. Azis Muthalib; Muh. Nur (Jurnal Syntax Admiration, 2024)
This study aims to determine and analyze specifically how each factor—work culture, work discipline, and work experience—impacts employee performance. This research is explanatory. An explanatory study generally aims to explain the position of the variables studied and the relationship and influence between one variable and another. Based on the research findings, it can be concluded that work culture, work discipline, and work experience have a positive and significant influence on employee performance at the West Kendari District Office. Improvements in work culture, work discipline, and work experience each significantly improve employee performance. That is, any improvement in these three factors will contribute to the improvement of employee performance at the West Kendari District Office.